1997
DOI: 10.5636/jgg.49.523
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Rock Magnetic Parameters and Paleointensities over a Single Holocene Lava Flow.

Abstract: A recent (2000 BP) lava flow from central Mexico has been sampled along a vertical profile with 55 cores covering a total flow thickness of 6.6 m. A wide range of physical and magnetic parameters have been studied to characterise the samples: Curie temperature and saturation magnetisation as intrinsic properties; density, magnetic susceptibility and remanence intensity as bulk properties; Konigsberger Qfactor and hysteresis parameters as coercivity parameters. All parameters vary smoothly over the profile, mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 26 publications
4
27
0
Order By: Relevance
“…In general, we agree with the opaque mineral description of samples from the lowermost part of the Xitle lava flows by Böhnel et al (1997), pointing to the presence of small euhedral titanomagnetites and ilmenites, in disseminated form or with skeletal textures. The state of oxidation of titanomagnetites mineral series is C2, for skeletal grains, but some subhedral grains with C3-C5 are also present.…”
Section: Microscopysupporting
confidence: 74%
See 1 more Smart Citation
“…In general, we agree with the opaque mineral description of samples from the lowermost part of the Xitle lava flows by Böhnel et al (1997), pointing to the presence of small euhedral titanomagnetites and ilmenites, in disseminated form or with skeletal textures. The state of oxidation of titanomagnetites mineral series is C2, for skeletal grains, but some subhedral grains with C3-C5 are also present.…”
Section: Microscopysupporting
confidence: 74%
“…At this point, it should be mentioned that the Xitle flow probably cooled down within a time span much shorter than the typical periods of geomagnetic intensity variations. The cooling time of 150 days proposed by Böhnel et al (1997) suggests that a geomagnetic origin for the observed PI variations is excluded. This is supported by the directional data, which are uniform throughout the flow.…”
Section: Discussionmentioning
confidence: 99%
“…For accepted samples the NRM fractions used for paleointensity determination range from 0.36 to 0.98 and the quality factors varies between 5 and 10, being normally greater than 5 (Table 1). Similarly to previous studies (Böhnel et al, 1997(Böhnel et al, , 2003Morales et al, 2001Morales et al, , 2003, where both conventional and microwave methods are involved, our selected paleointensity data (positive pTRM checks, NRM fraction higher than 1/3 and the quality factor higher than 5), yield unacceptable scatter for a single lava flow ranging from 49.0 to 73.42 μT and giving a mean of 61.4 ± 7.2 μT. Paleomagnetic data from a single cooling unit provides a spot reading of the paleofield, and the paleointensity scatter observed within single Xitle lava has no geomagnetic origin.…”
Section: Resultsmentioning
confidence: 66%
“…et al., 1965;Bucha et al, 1970;Lee, 1975;Aitken et al, 1991;Gonzalez et al, 1997;Böhnel et al, 1997;Morales et al, 2001;Böhnel et al, 2003;Morales et al, 2006), no serious attempts have been undertaken to study the rich cultural heritage of the region. The study reported here presents the first archeointensity survey from Mesoamerica and is part of the effort to establish an archeointensity variation curve for the region.…”
Section: Introductionmentioning
confidence: 99%